Interview of Donald Carpenter by Brian Shoemaker - Carpenter, Donald (Byrd Polar Research Center Archival Program, 2008)
1. Bob Helliwell-pp.1,2,11-14,21-24,27-28,32,35 2. Ed Coleman-pp.5-7,9-10 3. Kingsley Davis-pp.11 4. Mollet Morgan-pp.12 5. Owen Story-pp.13,21,26 6. John Katsavrakas-pp.14,27,41 7. Thorrie-pp.21 8. Bob Smith-pp.21-22 9. Neil Brice-pp.23-24,30 10. John Behrendt, pp.24 11. Martin-pp.25 12. Ernst Gehrels-pp.26 13. Arnold Shostak-pp.27 14. Irene Peden-pp.28 15. Myron Swaron-pp.28 16. Don Reynolds-pp.28 17. Run Sefton-pp.31 18. Chung Park-pp.31 19. Michael Trimpi-pp.32-34,48,51 20. Mollet Morgan-pp.34 21. Bob Vanowski-pp.35 22. Constantine Greengals-pp.36-37 23. Sig Bauer pp.38 24. Ev Pascal-pp.41,46 25. Bill Tabucco-pp.41,46 26. Paul Kentner-pp.44 27. John Billay-pp.43 28. Ted Rosenburg-pp.45 29. Rob Flint-pp.45-46 Dr. Carpenter and parents moved from Spokane, Washington to Portland, Oregon when he was 5 years old. His two grandfathers were faculty members at two different universities. His father became leader of communications for Northwest Bell. Dr. Carpenter’s first degree was in political science. While in the U.S. Navy he went to an electronics school and later was called for the Korean War. Academics were very important to him, though he was unfocused for a time. He studied a variety of subjects, including Russian at Columbia University. After not being cleared for positions with the U.S. Information Agency and with the CIA, he enrolled in electrical engineering at Stanford. As a student, he was looking at the data from the "Whistler’s West" IGY program. Research workers were studying the influence of large solar storms on communications; they determined that the plasma around the earth diminished in density. Carpenter observed that the change in density was greater at the higher latitudes then at lower latitudes. Low frequency radio waves can interact with particles. He deduced the sharp discontinuity in space. The whistlers would reflect back and forth along the magnetic field. Siple Station in Antarctica was located to receive whistler activity from a wide range of latitudes. From the data collected in 1963 and 1965 Carpenter was able to describe the plasmashere. Dr. Carpenter stresses the contributions of persons like Mike Trimpi, who have unique talents in designing and collecting field data. Constantine Greengals, a Russian scientist, collected data that supported the drop in density. The data supported Carpenter’s data, but scientists in both countries were not convinced. He described the use of rockets launched from Siple Station in 1980-81 to observe properties of the wave as it entered the ionosphere. Rob Flint directed a project at the Plateau Station to study the inactions of the low frequency radio noise with the optical emissions (Southern Lights), Dr. Carpenter describes the tug-of-war between the earth and the sun on the plasma. Although radiation from the sun produces currents on earth, he is not sure that the sun causes "space weather". Major Topics 1. As a graduate in electrical engineering, to analyze data about the "whistlers"; and lead to study of plasmapause. 2. School years were spent in Portland, Oregon. 3. Years in undergraduate studies and in military service are described. 4. At Whistler’s West network, found that the clearest tones came from lightning. 5. The changes in whistler activity related to the distribution of charge particles with height and associated with solar storms. 6. Something was causing the earth’s plasma to greatly diminish in density. 7. Propagation velocity of a pulse or wave packet along the Earth’s magnetic field is slower than the speed of light in a vacuum, a slow wave. 8. By placing a station at each end of the magnetic field, e.g. Byrd Station and Great Whale River, Canada, whistlers and other natural noises could be studied. 9. During the IGY, Carpenter compared the characteristics of whistlers received at various stations. He was able to deduce from the data that there is a sharp discontinuity in space. 10. The Eight Station in Antarctica had no local lightning activity. They verified that not only direct signals from the Navy transmitters but also delayed signals could be received. 11. Cold plasma provides the propagation medium for waves but hot plasma can exchange energy. 12. Siple was an ideal station because it was on a stable ice sheet, a conjugate point, signals could be received in an accessible region of Canada, and saw abundant whistler activity from many latitudes. 13. The studies of the wave environment of the earth were extended by using orbiting geophysical observations. Funded by a grant from the National Science Foundation.